Metabolic Effects of Doxorubicin on the Rat Liver Assessed With Hyperpolarized MRI and Metabolomics - Timm, Kerstin N.; Ball, Vicky; Miller, Jack J.; Savic, Dragana; West, James A.; Griffin, Julian L.; Tyler, Damian J. (Frontiers in Physiology, 2022)
Doxorubicin (DOX) is a successful chemotherapeutic widely used for the treatment of a range of cancers. However, DOX can have serious side-effects, with cardiotoxicity and hepatotoxicity being the most common events. Oxidative stress and changes in metabolism and bioenergetics are thought to be at the core of these toxicities. We have previously shown in a clinically-relevant rat model that a low DOX dose of 2 mg kg-1 week-1 for 6 weeks does not lead to cardiac functional decline or changes in cardiac carbohydrate metabolism, assessed with hyperpolarized [1-13C]pyruvate magnetic resonance spectroscopy (MRS). We now set out to assess whether there are any signs of liver damage or altered liver metabolism using this subclinical model. We found no increase in plasma alanine aminotransferase (ALT) activity, a measure of liver damage, following DOX treatment in rats at any time point. We also saw no changes in liver carbohydrate metabolism, using hyperpolarized [1-13C]pyruvate MRS. However, using metabolomic analysis of liver metabolite extracts at the final time point, we found an increase in most acyl-carnitine species as well as increases in high energy phosphates, citrate and markers of oxidative stress. This may indicate early signs of steatohepatitis, with increased and decompensated fatty acid uptake and oxidation, leading to oxidative stress.